Ответы и объяснения

2014-03-17T20:40:11+04:00
2sinx*cosx + \sqrt{3} - 2cosx - \sqrt{3}sinx = 0\sqrt{3}(1-sinx) - 2cosx(1-sinx) = 0 
(1-sinx)(\sqrt{3}-2cosx) = 0 
1-sinx = 0   или 2cosx = sqrt(3)
 sinx=1
x = \frac{\pi}{2}+2\pi n,  n - целое
cosx = \frac{\sqrt{3}}{2} 
x = \frac{\pi}{6}+2\pi n, n - целое 
Спасибо ,но может Вы как-нибудь отредактируете решение? А то не понятно..(
2sinx*cosx + sqrt{3} - 2cosx - sqrt{3}sinx = 0
sqrt{3}(1-sinx) - 2cosx(1-sinx) = 0

(1-sinx)(sqrt{3}-2cosx) = 0

1-sinx = 0 или 2cosx = sqrt(3)

sinx=1

x = frac{pi}{2}+2pi n, n - целое

cosx = frac{sqrt{3}}{2}

x = frac{pi}{6}+2pi n, n - целое
всё равно ничего не понятно(